Intermixing of Commercial Pure Breed Chickens with Indigenous (Sakini) Breed of Nepal - Amatya Gorkhali, Neena; Sherpa, Chhiring; Kolachhapati, Mana Raj; Pokharel, Bhoj Raj; Bhattarai, Nirajan; Sapkota, Saroj (Journal of Nepal Agricultural Research Council, 2021)
The intermixing of pure breeds of commercial chickens with Nepalese indigenous flock of chickens has not been explored yet genetically. The study aims to investigate the status of interbreeding of Nepalese indigenous chickens with exotic breeds. Thirty three samples of indigenous chicken, Sakini, from three different ecological regions, Terai, mid-hill and high hill, were taken for the study. The 522 bp hyper-variable region of D loop mtDNA of each sampled population was PCR amplified and sequenced. The Neighbor joining tree revealed that most of Nepalese Sakini and commercial chickens such as New Hampshire, Rhode Island Red, White Leghorn, White Plymouth Rock and Barred Plymouth Rock lied in same clade. Our study provides first direct evidence that the Sakini was already bred with commercial breeds for the sake of enhancing production performance and also alarms the government to introduce proper strategies and policies to avoid such genetic erosion.